Evaluasi Pelatihan Manajemen Keorganisasian Dalam Program Trailer Dengan Menggunakan Model Kirkpatrick - Siska Maulidya; Suci Indah Larassati; Ulfa Nur Fajariya; Syifaus Salwa; Mahesa Rangga Maulana; Hesti Kusumaningrum (Pusat Riset dan Inovasi Nasional, 2025)
Education requires leaders who not only have academic knowledge, but also strong leadership skills to manage, direct, and motivate teams in achieving increasingly complex educational goals. In the midst of changing needs of educational organizations, leadership training programs, such as Training of Leadership in Educational Management or TRAILER for short, have become essential to equip educational leaders with relevant skills. However, the implementation of this training program requires proper evaluation so that its success can be measured objectively and purposefully. The evaluation model that is suitable for this program is Kirkpatrick. The aim of this research is to analyze participant satisfaction with training methods and materials, analyze increased knowledge and organizational skills, analyze the application of skills in the campus environment and analyze the impact on organizational performance results. This research was conducted using a quantitative method approach and a qualitative method. The data collection technique carried out by the researcher was a questionnaire. The research results show that the TRAILER program has succeeded in creating an interactive training environment and supporting the development of student leadership skills.